Persistent organic pollutants in soils and sediments from James Ross Island, Antarctica - Klánová, Jana; Matykiewiczová, Nina; Mácka, Zdenek; Prosek, Pavel; Láska, Kamil; Klán, Petr (Environmental pollution (Barking, Essex, 2008)
Soil and sediment samples from James Ross Island were analyzed for their PCB, OCP and PAH contents. Soil concentrations ranged between 0.51 and 1.82 ng g(-1) for seven indicator PCB congeners, between 0.49 and 1.34 ng g(-1) for HCH congeners, between 0.51 and 3.68 ng g(-1) for the sum of p,p'-DDT, DDE, and DDD, and between 34.9 and 171 ng g(-1) for the sum of 16 EPA PAHs. Sediment levels from 0.32 to 0.83 ng g(-1) were found for PCBs, from 0.14 to 0.76 ng g(-1) for HCHs, from 0.19 to 1.15 ng g(-1) for DDTs, and from 1.4 to 205 ng g(-1) for PAHs. A prevalence of low-mass PAHs, less chlorinated PCBs, and more volatile chemicals indicates that the long-range atmospheric transport from populated areas of Africa, South America, and Australia is the most probable contamination source for the solid matrices in James Ross Island.
Keywords: látky znečišťující životní prostředí; polycyklické aromatické uhlovodíky; Environmental Monitoring; Hydrocarbons, Chlorinated; geologické sedimenty; Pesticides; polychlorované bifenyly; monitorování životního prostředí; Antarctic Regions; Environmental Pollutants; půda; pesticidy; Soil; Antarktida; chlorované uhlovodíky; Polycyclic Aromatic Hydrocarbons; Polychlorinated Biphenyls; Geologic Sediments